The Ethical Implications of Employing Socially Assitive Robots in the Aged-care Sector in Japan - Stirbat, Teodora Octavia (Student Undergraduate Research E-journal!, 2019)
Ground-breaking innovations in technology depict a promising future for humanity. In particular, the robotic industry is expected to solve many of our modern challenges especially with regard to the health sector. As expected, when introducing human-robot interactions in our daily lives, we need to renegotiate our human values in terms of autonomy, control and privacy. This paper aims to explore the ethical dilemmas occurring when employing socially assistive robots in the aged-care sector. It will also make recommendations for future ethical use of social robots. The cultural background is set in Japan, a leader in robotic development. “Permission to make digital or hard copies of all or part of this work for personal or classroom use is granted under the conditions of the Creative Commons Attribution-Share Alike (CC BY-SA) license and that copies bear this notice and the full citation on the first page” Connection with SDG 9 The Sustainable Development Goals number 9 refers to building resilient infrastructure, promote sustainable industrialization and foster innovation. These actions are highly dependent on technological innovations. In order to create long-term sustainable structures, we need to welcome advancements in our life but in the same time treat them carefully. This paper tackles one of the recent technological advancements in the field of robotics. Socially Assitive Robots have been designed to help children, people with disabilities and elders in a social, non-intrusive and positive way. In spite of this, ethical dilemmas which clash with the design of the robots are not often taken into account. That is why, the research is meant to fill in the gap and prove that an ethical sustainable goal can be met by responsible advancements in technology.